(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Maternal lifestyle has been implicated as a predisposing factor in the development of metabolic disorders in adulthood. This lifestyle includes the immediate environment, physical activity and nutrition. Maternal nutrition has direct influence on the developmental programming through biochemical alterations and can lead to modifications in the fetal genome through epigenetic mechanisms. Imbalance in basic micro or macro nutrients due to famine or food deficiency during delicate gestational periods can lead to onset of metabolic syndrome including obesity. A major example is the Dutch famine which led to a serious metabolic disorder in adulthood of affected infants. Notably due to gene variants, individualized responses to nutritional deficiencies are unconventional, therefore intensifying the need to study nutritional genomics during fetal programming. Epigenetic mechanisms can cause hereditary changes without changing the DNA sequence; the major mechanisms include small non-coding RNAs, histone modifications and most stable of all is DNA methylation. The significance association between obesity and DNA methylation is through regulation of genes implicated in lipid and glucose metabolism either directly or indirectly by hypomethylation or hypermethylation. Examples include CPT1A, APOA2, ADRB3 and POMC. Any maternal exposure to malnutrition or overnutrition that can affect genes regulating major metabolic pathways in the fetus, will eventually cause underlying changes that can predispose or cause the onset of metabolic disorder in adulthood. In this review, we examined the interaction between nutrition during gestation and epigenetic programming of metabolic syndrome.